2020
DOI: 10.5194/acp-2020-213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal variations in the high time-resolved aerosol composition, sources, and chemical process of background submicron particles in North China Plain

Abstract: Abstract. For the first time in the North China Plain (NCP), we investigated the seasonal variations of submicron particles (NR-PM1) and its chemical composition at a background mountain station using Aerodyne high-resolution time-of-flight aerosol mass spectrometry (HR-ToF-AMS). The averaged NR-PM1 were highest in autumn (15.1 μg m−3) and lowest in summer (12.4 μg m−3), with the abundance of more nitrate in spring (34 %), winter (31 %), and autumn (34 %), and elevated organics (40 %) and sulfate (38 %) propor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…The average increase rate of sulfate was the largest (0.4 µg m −3 h −1 ) among NR-PM 1 species, while that of NR-PM 1 was 0.8 µg m −3 h −1 . These results also suggested that the photochemical aging process plays an important role in sulfate formation in summertime (Li et al, 2020). Previous studies have revealed that an aqueous-phase process plays an important role in sulfate formation (Sun et al, , 2013a.…”
Section: Role Of Photochemical Aging In Aerosol Formation and Compositionsupporting
confidence: 67%
See 1 more Smart Citation
“…The average increase rate of sulfate was the largest (0.4 µg m −3 h −1 ) among NR-PM 1 species, while that of NR-PM 1 was 0.8 µg m −3 h −1 . These results also suggested that the photochemical aging process plays an important role in sulfate formation in summertime (Li et al, 2020). Previous studies have revealed that an aqueous-phase process plays an important role in sulfate formation (Sun et al, , 2013a.…”
Section: Role Of Photochemical Aging In Aerosol Formation and Compositionsupporting
confidence: 67%
“…Typically, the fraction of OA (48.3 %) in suburban Beijing is higher than those in urban Beijing (33 %-38 %), while the contribution of SIA (51.7 %) in suburban Beijing is smaller than those in urban Beijing (58 %-64 %) (Hu et al, 2017;Huang et al, 2010;Sun et al, 2010Sun et al, , 2012. The reason may be the difference in the emissions of gaseous precursors (e.g., SO 2 and NO x ) and their conversion ratio to SIA (Hu et al, 2017;Li et al, 2020). Meanwhile, the inorganic sulfate, nitrate, and chloride could be well neutralized by ammonium during this field observation since there is an extremely good linear relationship between NO 3 + 2 • SO 4 + Cl and NH 4 (R 2 = 0.998, slope = 0.992 ± 0.002, Fig.…”
Section: Chemical Compositions Of Pmmentioning
confidence: 97%
“…The average increase rate of SO4 2was the largest (0.4 μg m -3 per hour) among NR-PM1 species, while that of NR-PM1 was 0.8 μg m -3 per hour. These results also suggested that the photochemical aging process plays an important role in SO4 2formation in summertime (Li et al, 2020). Previous studies have revealed that an aqueous-phase process plays an important role in SO4 2formation Sun et al, 2013a).…”
Section: Role Of Ta In Aerosol Formation and Composition 243supporting
confidence: 67%
“…their conversion ratio to SIA (Li et al, 2020;Hu et al, 2017). Meanwhile, the inorganic SO4 2-, NO3 -, and Clcould be well neutralized by NH4 + during this field observation since there is an extremely good linear relationship between NO3 -+2×SO4 2-+Cland NH4 + (R 2 = 0.998, slope = 0.992 ± 0.002, Fig.…”
Section: Chemical Compositions Of Pm1mentioning
confidence: 70%